Training on Safe Use of Information and Cybersecurity in the Higher Education System - Djurayev Iqbol Iloyovich (Zien Journals, 2022)
this article provides scientific grounds for ensuring information security and cybersecurity in the system of continuing education, as well as its activation and protection of youth from information attacks
Keywords: Information Security; Hacker; cybersecurity; Case-study